Pengaruh Word of Mouth terhadap Minat Beli Serta Dampaknya pada Keputusan Pembelian Wifi Muzan Net - Ajeng Auliana Putri; Ujang Syahrul Mubarok; Taufik Akbar (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to examine the influence of word of mouth on buying interest and its impact on the purchase decision of Muzan Net wi-fi services. This study uses three main variables, namely independent variables, bound variables, and intervening variables. The free variable is word of mouth, the bound variable is the purchase decision, while the intervening variable is the buying interest. The research sample consisted of 55 consumer respondents who knew and used the Muzan Net wi-fi service in Sanggrahan Village. Research data was obtained through questionnaires, observations, and interviews, with sampling techniques using the simple random sampling method. Data analysis is carried out through several stages, namely measurement or outer model, structural model or inner model, and hypothesis test. The results of the study show that word of mouth has a positive and significant effect on buying interest. Furthermore, word of mouth also has a positive but not insignificant effect directly on the purchase decision. Meanwhile, buying interest has been proven to have a positive and significant effect on purchase decisions. In addition, buying interest is able to mediate the relationship between word of mouth and purchase decisions, thereby strengthening the role of word of mouth in encouraging consumers to finally make a purchase decision. This research provides practical benefits for companies in maximizing word-of-mouth-based marketing strategies, as well as a reference for future research to develop similar studies with different objects, locations, and variables.